Adaptation of the vesicle assay for rapid screening of the membrane interacting compounds from plants - Mai Phuong, Nguyen Thi; Truc, Trinh Anh (Academia Journal of Biology, 2014)
A key problem in identifying drug candidates from biological materials is a rapid and effective screening method. The goal of this work is to adapt and demonstrate that the artificial lipit bilayer model can be used as a simple colorimetric assay for rapid screening of pharmaceutical compounds, especially cationic antimicrobial peptides (AMPs) from the crude extracts of biological materials, that can interact with artificial lipit barriers. The obtained data showed that the model worked well for the evaluation of drug penetration across the lipit barrier made from a vesicles solution containing phospholipits dimystoylphosphatidylcholine (DMPC) and polydiacetylene (PDA), as well as mechanism of the drug action. Moreover, the system could be used for rapid screening of AMPs from different genetic resources such as plants, microorganisms, animal tissues. The different colorimetric response (CR) of the compounds to the vesicle solution was estimated by %CR value, which was calculated based on the ratio of absorbance of the indicator at the wavelength 640 nm (blue color) and 500 nm (red color). Among 9 plant crude extracts in 20 mM Tris - HCl pH 7.0 were examined, including Brassica juncea L. (as a positive control); Acacia mangium; Sesbania sesban (L.) Merr.; Pachyrrhizus erosus (L.) Vrb.; Taramindus indica L; Leucaena leucocephala (Lam) De Wit 3; Acacia difficilis; Gleditsia fera (Lour.) Merr; Cassia tora L., the extracts of Brassica juncea L. and Cassia tora L exhibited the highest values of %CR compared to the other samples suggesting that they are containing membrane interacting compounds, probably AMPs. The antifungal/antimicrobial activity of Cassia tora L extract was also determined in terms of the growth inhibition of the plant fungus Fusarium oxysporum and the dental caries bacterium Streptococcus mutans. The preliminary results showed that the extract at protein concentration of 1.7 mg/ml did not inhibit the growth of Fusarium oxysporum but inhibited the growth of dental caries bacterium Streptococcus mutans. Further work is going on to characterize the antimicrobial agents in this plant.